2005
DOI: 10.1161/01.atv.0000151874.81059.ad
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Triglyceride Synthesis as a Treatment Strategy for Obesity

Abstract: Abstract-Because the ability to make triglycerides is essential for the accumulation of adipose tissue, inhibition of triglyceride synthesis may ameliorate obesity and its related medical consequences. Acyl coenzyme A (CoA):diacylglycerol acyltransferase 1 (DGAT1) is 1 of 2 DGAT enzymes that catalyze the final reaction in the known pathways of mammalian triglyceride synthesis. Mice lacking DGAT1 are resistant to obesity and have increased sensitivity to insulin and leptin. DGAT1-deficient mice are also resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 30 publications
2
116
3
3
Order By: Relevance
“…DGAT1 is the enzyme which catalyzes the final step in the TG synthesis pathway and considered to play key regulatory role in TG synthesis (Chen and Farese 2000). DGAT1-deficient mice showed a reduced adipose mass in comparison to wild-type mice on a chow diet (Smith et al 2000;Chen and Farese 2005). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DGAT1 is the enzyme which catalyzes the final step in the TG synthesis pathway and considered to play key regulatory role in TG synthesis (Chen and Farese 2000). DGAT1-deficient mice showed a reduced adipose mass in comparison to wild-type mice on a chow diet (Smith et al 2000;Chen and Farese 2005). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitro studies have revealed that DGAT1, but not DGAT2, is a multifunctional acyltransferase able to catalyze the synthesis of DAG, retinyl esters and waxes, in addition to TAG [35]. The functional differences between these two enzymes are further emphasized by studies in mice lacking DGAT1 and 2 [34,[36][37][38][39]. While mice lacking DGAT2 have a drastic reduction in whole body TAG and die shortly after birth, mice lacking DGAT1 are viable, have improved insulin sensitivity, demonstrate modest reductions in tissue TAG and are resistant to diet-induced obesity.…”
Section: Biosynthesis Of Triacylglycerolmentioning
confidence: 99%
“…78 Inactivation of anabolic enzymes of fatty acid uptake and storage enhanced tissue glucose disposal or insulin secretion whereas disruptions in the catabolic process tended to impair insulin action or secretion. 79,80 Overexpression of DGAT1 in AT yields a mouse that is more obese but also more insulin sensitive. 81 In human AT, DGAT1 and fatty acid synthase expression are strongly correlated with insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%